Stage of breast cancer at diagnosis among women with cosmetic breast implants - Hölmich, L R (Nature Publishing Group, 2003)
Concern has been raised about the potential delay in breast cancer diagnosis in the augmented breast. We linked a cohort of 2955 women, who received cosmetic breast implants in Denmark during the period 1973–1997 with the Danish Cancer Registry and the Danish Breast Cancer Cooperative Group register. We identified 23 incident cases of invasive breast cancer diagnosed subsequent to breast implantation. We randomly selected 11 controls for each case from the Danish Breast Cancer Cooperative Group's register, and obtained detailed information on all study subjects about surgery, histopathology and stage of breast cancer at diagnosis, intended adjuvant treatment according to trial protocols and overall survival. We found that women with breast implants on average were diagnosed with breast cancer at the same stage as controls. Significantly more women with breast implants had tumour cells in the surgical margins according to the Danish Breast Cancer Cooperative Group's data. There was no significant difference in overall survival between the two groups after an average of 6.4 years of follow-up. Based on this limited number of women with breast cancer subsequent to breast augmentation, breast implants do not appear to delay the diagnosis of breast cancer, and no evidence of impaired survival after breast cancer diagnosis in augmented women was found.